Variation in football players' sprint test performance across different ages and levels of competition - Abrantes, C.; Macas, V.; Sampaio, J. (Journal of Sports Science & Medicine, 2004)
The purpose of this study was to compare sprint test performance performed by football players of different ages and levels of competition. One hundred and forty six Portuguese players from different teams completed the test (seven maximal sprints interspersed with 25 s active recovery). A 6 (level of competition: 1st national division, 2nd national division, 1st regional division, sub 16, sub 14, sub 12) 7 (sprint trial: sprint 1, sprint 2, sprint 3, sprint 4, sprint 5, sprint 6, sprint 7) repeated measures ANOVA was carried out on subjects sprint times. The main effect of level of competition was statistically significant, F(5, 140) = 106.28, p < 0.001. Subjects from 1st national division were significantly faster than subjects from 2nd national division; subjects from 1st regional division obtained similar performances when compared to sub 16 and sub 14 level; subjects from sub 12 level were the slowest. The main effect of sprint trial was also statistically significant, F (6, 840) = 7.37, p < 0.001. Mean sprint times from the first trial were significantly slower than mean sprint times from the second, third and fourth trial. Results from the fifth, sixth and seventh trials were slower, denoting a decrement in performance. The two main effects were qualified by a significant level of competition x sprint trial interaction, F (30, 840) = 9.47 p < 0.001, identifying markedly different performance profiles. Coaches should be aware that normative data regarding this test can play a very important role if used frequently and consistently during the whole season.